Residual amino-acid fluxes in the upper water column of the bransfield strait - Liebezeit, G (Gauthier-Villars, 1985)
Fluxes of residual amino acids were determined on samples from two drifting sediment traps deployed at 100 rn water depth in the Bransfield Strait in December 1980. Differences in the absolute fluxes were related to the sources of sedimenting particulate matter. The relative contributions of amino acids to the total flux and the molar composition were similar for both traps. Comparison with published particulate amino acid fluxes indicates that a distinction must be made between high and low production environments. In the former case, 90% of the primary amino acid production is degraded within the upper 100 metres of the water column, whereas in the latter case this zone is extended to approximately 1,000 m. Les flux d'acides aminés résiduels ont été estimés sur des échantillons issus de pièces à sédiments dérivants, déployés à 100 rn de profondeur dans le détroit de Bransfield en décembre 1980. Les différences observées dans les flux absolus sont reliées aux sources du matériel particulaire sédimenté. La contribution relative et la composition molaire des acides aminés participant au flux total sont identiques d'un piège à l'autre. La comparaison des flux entre nos résultats et ceux de la littérature indique qu'une distinction doit être faite entre des milieux à forte et à faible production. Dans le premier cas, 90% de la production d'acides aminés sont dégradés dans les 100 premiers mètres de la colonne d'eau; tandis que dans l'autre cas, cette couche peut atteindre environ 1 000 m.